Konsep Cinta kepada Allah Menurut Zulfikar Ahmad Naqshabandi (Studi Kasus Pernikahan Ta’aruf di Kelurahan Paya Pasir Kecamatan Medan Marelan) - Harahap, Diana Sari; Adenan, Adenan; Nasution, Kasron (Lembaga Yasin AlSys, 2023)
This study looks at the idea of love for Allah as explained by Zufikar Ahmad Naqshabandi. The researcher will try to explain the ideas of Mahabbah Zulfikar Ahmad Naqshabandi and what love for Allah looks like in practice. In Paya Pasir Village, Medan Marelan District, Ta'aruf Marriage is used by researchers as an illustration of how love for God is shown. Ta'aruf is designed to help people get to know each other's personality, background, social, culture, education, family, and religion. This type of research is qualitative, which uses a series of sentences to describe the data. Descriptive method used in this research.The findings of this study suggest that Zulfikar Ahmad Naqshbandi's definition of love for Allah Swt. is correct: deep love for Allah Swt. is a proof of flawless faith. This love endures through the ages, undeterred by how life's circumstances change constantly. Marriage in Ta'aruf is a sign of being a lover of Allah SWT with an approach to love for Him. By abstaining from the forbidden and following His instructions. Then offer what has been predetermined to Allah Swt.